A Framework For Evaluating Information Quality Of Persian Weblogs - Kargar Bideh, Mohammad Javad (2008)

(untitled)
The World Wide Web is a great tool for exploring all kinds of information. Unlike books and journals, most of this information is unfiltered, i.e. not subject to editing or peer review by experts. This lack of quality control and the large increase in number of web sites make the task of finding quality information on the web especially critical. Meanwhile, new facilities for producing web pages such as weblogs make this issue more significant because Blogs are simple content management tools that enable non-experts to build easily updatable web diaries or online journals. Despite a decade of active research, a comprehensive methodology for the assessment of Information Quality (IQ) is lacking. Specifically, no framework for measuring information quality on the weblogs is currently available.After identifying and prioritizing IQ criteria on Weblogs, a Weblog management system that automatically calculates and collects IQ scores for created Weblogs is developed. The system is implemented on Persian Weblogs. Results of analysis of data collected by the Weblog management system show that there are significant correlations between many of the information quality variables. In addition, an analysis of the data revealed seven IQ dimensions on the Weblogs. Each of the dimensions was comprised of related IQ variables. Coefficients are identified for each variable in order to facilitate IQ measurement on the Weblogs. Moreover, statistical analysis shows that three specific sub-criteria for Weblogs; namely the number of written comments, number of received comments and comment per entry influence information quality on the Weblogs and interestingly fall into same dimension.